Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Pertambangan - Suciyanah; Hotang, Keri Boru; Ronauli, Egi (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2022)
This study aims to determine the effect of profitability, financial performance, capital structure on sharia stock prices. The independent variables in this study are profitability, financial performance and capital structure. The dependent variable is stock price. The research method uses quantitative methods. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) during 2018- 2019. The sample of this study were 36 companies listed on the Indonesia Stock Exchange (IDX) obtained by purposive sampling. The analysis technique used in this study is multiple linear regression. The results showed that profitability measured by Return on Assets (ROA) had a significant negative effect on Capital Structure and Company Size (Size) measured by Ln total assets did not significantly influence Capital Structure